Towards a history of Acceptance and Commitment Therapy (ACT) in Brazil: some fragments - Vandenberghe, Luc; Cunha, Olivia Rodrigues da (Perspectivas em Análise do Comportamento, 2025)
This article considers the conceptual trajectory of Acceptance and Commitment T herapy (ACT) and its dissemination in Brazil. It describes how ACT was thought, in a context strongly influenced by Experimental Behavior Analysis, as an alternative to CognitiveBehavioral Therapy. ACT was inspired by experimental studies on verbal control and rulefollowing, and contextualist philosophy. Presented by Steven Hayes during visits to Brazil, the approach and on contextualist philosphy was adopted early on by certain groups of behavioral therapists, who saw in ACT a coherent solution for working with thoughts and emotions. However, there there was slight approval of approval from the orthodox leadership of Behavior Analysis, which made it difficult to disseminate ACT outside these small groups. After two decades of limited visibility, another generation of therapists became familiar with ACT at international events, and young researchers showed interest in Relational Frame Theory (RFT), lending ACT a certain scientific respectability. Also driven by driven by the demand created by a new wave of students in behavioral therapy, ACT was consolidated in Brazil within the national clinical scenario, differing from, yet in dialogue with, Behavioral Analytical Therapy.